ANALYSIS OF AGREEMENT ON THE CONSTRUCTION OF MOSQUE INTERIORS IN THE PERSPECTIVE OF AL-IJĀRAH ALA AL- 'AMĀL CONTRACT - Najimi, Ahmad; Saifullah Karam (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
The practice of Borongan work agreement on the manufacture of mosque interiors between CV Serba Na Plafon and the mosque BKM is carried out in the form of an oral agreement, and both parties have agreed to the contents of the agreement. However, after the work was completed and the work contract ended, there was damage to the interior of the mosque, and the BKM mosque asked for responsibility for CV Serba Na Plafon. This study examines the work agreement between the management of the BKM Mosque and the contractor in making the interior of the mosque and the review of the al-ijārah ala al-amāl contract on the agreement and implementation of mosque interior design work in Southwest Aceh Regency. This research is a descriptive qualitative research analysis with a normative sociological approach, where the data obtained comes from observations and interviews. Based on the results of the research, it was found that: first, the work agreement between the BKM and the contractor is carried out in the form of an oral agreement, in the agreement, a three-month warranty is given to complete the work, with the provision that if damage occurs, then all damage is not the responsibility of CV Seba Na Plafon. Second, the review of the al-ijārah ala al-amāl contract on the agreement and implementation of the mosque interior design work is not in accordance with the terms and conditions of the al-ijārah ala al-amāl contract. In its implementation, the BKM of the mosque asks for responsibility for damage to the interior of the mosque carried out by CV Serba Na Plafon, which should be according to the al-ijārah ala al-